EFEKTIFITAS SENAM HAMIL ONLINE TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS PRAMBON - Nurul Hidayah; Siti Mudrikatin; Happy Rina Mardiana (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2023)
Introduction: Low back pain is a common complaint experienced by pregnant women in the third trimester. Doing exercise during pregnancy can relieve lower back pain. Objective: This study aimed to determine the effect of online pregnancy exercise on reducing low back pain in third trimester pregnant women in the Prambon Health Center Work Area. Methods: This type of research is a quasy experiment with a one group pretest posttest design. The population of study were all pregnant women in the third trimester, totaling 35 pregnant women. The sampling technique used was total sampling. The independent variable of online pregnancy exercise and the dependent variable decreased low back pain. The research instrument uses observation. Data processing using editing, coding, scoring, tabulating with data analysis Paired t-test. Results: The results showed that before the online pregnancy exercise was carried out, most of the respondents experienced low back pain with a scale of 3(more painful) as many as 27 respondents (77,1%), a scale of 4(very painful) as many as 8 respondents(22,9%),while after the online pregnancy exercise was carried out, most of the respondents experienced low back pain with a scale of 3 (more painful) to a scale of 0 (no pain) as many as 20 respondents (57,1%) and a scale of 1 (slight pain) 7 respondents (20%),of respondents experiencing back pain with a scale of 4 (very painful) to a scale of 1 (slight pain) as many as 3 respondents (8,6%) and a scale of 2 (slightly more painful) as many as 5 respondents (14,3%).Paired statistical test t-test shows value = 0.000<(0.05) so that H1 is accepted. Conclusion: There is an effect of online pregnancy exercise on reducing low back pain in third trimester pregnant women.